Interventional oncology: A snapshot of expanding practice - Azzam Khankan (The Arab Journal of Interventional Radiology, 2017)
Interventional oncology (IO) was a minor part of interventional radiology. However, with the development of novel technologies and introduction of innovative therapeutics with dramatic transformations in the practice of oncology, IO is facing challenges in adopting and responding to these new changes to maintain its integral role and maximize its potentials in the efficient management of patients with cancer. In this snapshot, some of the novel therapeutic approach principles relevant to IO practice will be explained briefly.